FRIENDSHIP RELATIONS BETWEEN AISYIYAH BOARDING SCHOOL BANDUNG STUDENTS - Muhammad Ridho Albari; Ghaida Az-zahra Kusnadi; Kamila Suci; Muhammad Fadilah Noor Agustian; Mamat Supriatna; Nandang Budiman (Study Program Guidance and Counseling, Univesitas Pendidik, 2022)
During adolescence, success in interacting with their social environment, especially with their peers, will greatly affect the process of their further psychological development. SMP Aisyiyah Boarding School Bandung is one example of a school that has its own specialty, therefore, this research entitled